Four propositions about how valuation intervenes in local environmental politics. Issue 1 (10th November 2020) - Tadaki, Marc; Sinner, Jim; Šunde, Charlotte; Giorgetti, Annabelle; Glavovic, Bruce; Awatere, Shaun; Lewis, Nick; Stephenson, Janet
Abstract: Environmental valuation provides a way of soliciting and organising information about how people relate to their environments. By canvassing a broad spectrum of human–nature relationships, valuation practice seeks to make environmental decision‐making more inclusive of diverse human concerns and aspirations. When valuation is undertaken in real‐world decision‐making settings, choices must be made about how to adapt valuation into context. Generic guidance illuminates choices of theory and method, as well as practical issues such as cost and complexity; however, little guidance exists on how to understand and respond to the political implications of valuation in places. To address this, we develop four propositions on how valuation intervenes into conflicted environmental decision‐making contexts, drawing on interviews with government officials and marine values‐holders from Aotearoa New Zealand's Marlborough Sounds. Valuation intervenes in politics by (i) vesting certain scales and actors with authority, (ii) aligning with or contesting existing regulatory categories, (iii) reallocating expertise about the environment and (iv) reproducing or reworking the uneven playing field of decision‐making. Understanding these implications can support valuation practitioners to situate their work within locally relevant contexts and objectives. These propositions provide a way of grasping the mechanisms through which valuation intervenes in local political struggles for environmental authority. Using these prompts, and developing others, can help valuation practitioners to 'do good' through seeking place‐based environmental justice and sustainability. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.